2005
DOI: 10.1093/hmg/ddi078
|View full text |Cite
|
Sign up to set email alerts
|

SMNΔ7, the major product of the centromeric survival motor neuron (SMN2) gene, extends survival in mice with spinal muscular atrophy and associates with full-length SMN

Abstract: Spinal muscular atrophy (SMA) is an autosomal recessive disorder in humans which results in the loss of motor neurons. It is caused by reduced levels of the survival motor neuron (SMN) protein as a result of loss or mutation of the SMN1 gene. SMN is encoded by two genes, SMN1 and SMN2, which essentially differ by a single nucleotide in exon 7. As a result, the majority of the transcript from SMN2 lacks exon 7 (SMNDelta7). SMNDelta7 may be toxic and detrimental in SMA, which, if true, could lead to adverse effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

34
669
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 557 publications
(705 citation statements)
references
References 68 publications
34
669
1
1
Order By: Relevance
“…Even if the functional implications of the D7 protein are still debated, the FL/D7 ratio, measured at the mRNA level, is a valuable indicator of the effect of treatments that modulate SMN RNA splicing. 29,30 Moreover, we have also included into the same reaction an amplicon that measures total SMN transcripts. Any significant increase of this value should provide a direct indication of the effect of drugs that increase SMN transcription or SMN mRNA stability.…”
Section: Discussionmentioning
confidence: 99%
“…Even if the functional implications of the D7 protein are still debated, the FL/D7 ratio, measured at the mRNA level, is a valuable indicator of the effect of treatments that modulate SMN RNA splicing. 29,30 Moreover, we have also included into the same reaction an amplicon that measures total SMN transcripts. Any significant increase of this value should provide a direct indication of the effect of drugs that increase SMN transcription or SMN mRNA stability.…”
Section: Discussionmentioning
confidence: 99%
“…However, how suboptimal levels of SMN lead to SMA is largely unknown. Multiple studies in SMA mouse models revealed widespread synaptic defects in neuromuscular junctions (NMJs), including neurofilament accumulation, poor terminal arborization, immature endplates, reduced quantal content, disturbed calcium homeostasis, and decreased remodeling potential; these defects precede motor neuron death (Cifuentes-Diaz et al 2002;Le et al 2005;Jablonka et al 2007;Kariya et al 2008;Murray et al 2008Murray et al , 2012Kong et al 2009;Ling et al 2010;Ruiz et al 2010;Lee et al 2011), suggesting that the NMJ alterations are the initial consequence of SMN deficiency, Ó 2015 Hua et al This article is distributed exclusively by Cold Spring Harbor Laboratory Press for the first six months after the full-issue publication date (see http://genesdev.cshlp.org/site/misc/terms.xhtml). After six months, it is available under a Creative Commons License (Attribution-NonCommercial 4.0 International), as described at http:// creativecommons.org/licenses/by-nc/4.0/.…”
mentioning
confidence: 99%
“…Will the disease still develop if a correction of SMN2 splicing is discontinued after the first phases of post-natal life? Mouse models for SMA 28,29 and transgenic mice expressing the tTR-KRAB regulator 30 are available. If these genotypes are combined with the regulatable U7-ESE-B cassette, many of the above questions could be addressed, simply by providing doxycycline through drinking water at different times during ontogenesis.…”
Section: Discussionmentioning
confidence: 99%